ANALISIS EKSPOR KOMODITAS PERKEBUNAN TERHADAP PERTUMBUHAN PEREKONOMIAN DI PROVINSI SULAWESI SELATAN - Hamsiah, Hamsiah; Rahim, Abd. Rahman (COMPETITIVENESS, 2018)
This study aimed to determine and analyze the effect of export plantation commodities on economic growth in South Sulawesi. To know and analyze the export volume of plantation commodities, especially cocoa beans, coffee beans, cashew seeds, and rubber that affect the economic growth in South Sulawesi. And to know and analyze the effect of export trend of plantation commodities on economic growth in South Sulawesi. This research was conducted with the design of quantitative research method using time series data in the last 12 years.This results of the research shown 1) Export of plantation commodities such as cocoa beans, coffee beans, cashew seeds, and rubber had a mutual influence on economic growth in South Sulawesi in 2006 to 2017, 2) total exports of rubber commodities had a significant effect on economic growth in South Sulawesi, while cocoa beans, coffee beans, and cashew seeds had no significant effect, 3) trend analysis on total exports of plantation commodities such as exports of cocoa beans, coffee beans, cashew seeds, and rubber shown different trends. Commodities of cocoa beans, coffee beans, and rubber shows a negative trend while the commodity of cashew seeds had a positive trend and line. Keywords : Exports, Plantatioan Commodities, Economic Growth.